Estimation of the cost of an enterprise own capital with the account of financial risk of investment project - Y. S. Potashnik (Russian Journal of Economics and Law)
Objective: to specify and develop approaches to estimation of the cost of an enterprise own capital invested into the realization of investment projects, with the account of financial risks. Methods: logical analysis and synthesis, statistical analysis, method of pairwise comparison. Results: The concept was formulated and formalized referring to estimating the cost of the enterprise own capital used for investment project. The approaches were specified to define the cost of the enterprise own capital. The method was proposed to define the value of correcting the alternative profitability, if the viewed investment project differs by the financial risk level. Scientific novelty: The new method was proposed to define the value of correcting the alternative profitability, based on the quantitative estimation of financial risk credit by the credit establishments, under the certain investment decision. Practical value: The possibility to increase the reliability of estimation of the enterprise own capital, as well as validity of decisions referring to the selection and structure of investment projects financing.